2013
DOI: 10.1186/1756-3305-6-284
|View full text |Cite
|
Sign up to set email alerts
|

Ultra low concentration deltamethrin loaded patch development and evaluation of its repellency against dengue vector Aedes (S) albopictus

Abstract: BackgroundMosquito repellents and emanators confer protection against mosquito bites through spatial action of emanated vapours which are released into the adjoining environment. Synthetic insecticides released into the environment in ultra low volume vapour phase deter the mosquitoes from biting humans in a protected space.MethodsFormulation patches were prepared using the solvent evaporation method over a backing membrane and using Dibutylphthalate (DBT) as a plasticizer. The effect of formulation variables … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…DSC results obtained here indicated that the CWO was stable in pectin nanocapsules, which was produced by crosslinking with CaCl 2 . The comparable result was reported previously by Chattopadhyay et al 50 , who used DSC tool to study the compatibility between the polymer, active and other components of the formulations. In both the cases, the shift towards higher temperature was observed in the thermogram of the polymer loaded with active content.…”
Section: Resultssupporting
confidence: 89%
“…DSC results obtained here indicated that the CWO was stable in pectin nanocapsules, which was produced by crosslinking with CaCl 2 . The comparable result was reported previously by Chattopadhyay et al 50 , who used DSC tool to study the compatibility between the polymer, active and other components of the formulations. In both the cases, the shift towards higher temperature was observed in the thermogram of the polymer loaded with active content.…”
Section: Resultssupporting
confidence: 89%
“…In addition to their insecticidal effect, pyrethroids have both spatial repellent and contact irritant effects,[ 17 – 19 ] though excitorepellency is probably the most important effect when pyrethroids are used on clothing. Limited evidence suggests that pyrethroid-resistant populations may actually be more strongly repelled by pyrethroids and other repellents than fully susceptible mosquitoes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the current challenge refers to the need to protect people before they go to bed and while they are outdoors. One way of doing this might be to use repellents to prevent mosquitoes from biting and hence a number of products have been developed with this in mind (Kweka et al, 2012;Chattopadhyay et al, 2013;Revay et al, 2013).…”
Section: Introductionmentioning
confidence: 99%